EFFICIENCY ANALYSIS OF DRUG MANAGEMENT ON DISTRIBUTION AND USAGE LEVEL IN COMMUNITY HEALTH CENTERS - Abd Razak; Gunawan Pamudji; Mugi Harsono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug management in community health centers is conducted by the pharmacy section. Drug management problems in Sibela, Pajang and Nusukan health centers were that there were expired drugs and dead stock. The purpose of this study was to evaluate the efficiency of drug management in both use and distribution levels in Sibela, Pajang and Nusukan health centers. This research was conducted using retrospective and concurrent data. Data were collected in form of qualitative and quantitative data observations from existing document and interview with relevant officials. Then, the data were presented in tabular and textual description. The efficiency of drug management was measured at distribution and use stages using its indicators and compared with standard. The result showed that distribution and use of medicine in Sibela, Pajang and Nusukan health centers generally were not efficient. In Sibela and Pajang health centers, the level of drug availability were 53 and 68 days, respectively. The inefficiency of drug management in both health centers was shown in the percentage of expired drugs that accounts for 0.3% and 0.61%, and in the percentage of dead stock, that accounts for 4.6% and 20.40% respectively. In Nusukan health center, the level of drug availability was 40 days and there were no expired drugs. However, in Nusukan health center, the percentage of dead stock was 14.31% that was not efficient. Drug use in Sibela, Pajang and Nusukan health centers showed that the number of item of drugs per prescription was 3.17, 2.97 and 4, the percentage of generic drug per prescription was 91.85%, 93% and 88.10%, the demand of all medicines was fulfilled, the use of antibiotics for acute respiratory tract infection non-pneumonia was 1.87%, 0% and 1.20%, and the percentage of antibiotic use for non-specific diarrhea was 3.51%, 0% and 0.29, respectively.Keywords: medication management, indicators, efficiency, distribution, usage